COVID-19 Preparation at a Rural District Hospital in Nepal: The days following the lockdown - Aryal, Prayush (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Since the beginning of 2020 AD, the world is grappling with the COVID-19 pandemic and in Nepal, the first case was seen in the month of January itself. The second case, however, was detected only after 2 months and this gave the country an opportunity to upgrade the health system, especially for the pandemic. It also imposed a nationwide lockdown to contain the spread of the disease.Myagdi, a rural district of Nepal and its district hospital in Beni also prepared for the disease with the resources it had. The incoming route to the district was sealed off and people were asked to stay indoors unless there was an emergency. The regular OPD services of the hospital was also closed and a fever clinic was established where all the fever and suspected COVID-19 cases were seen.An isolation building was set up where the strong suspected cases were admitted and kept there until their PCR reports came out. Similarly, quarantine facilities were also made outside the hospital premises for those who had returned to the district from abroad. The hospital staffs were given Personal Protective Equipment, but they were scarce and had to be re-used. The whole scenario had appeared to put a mental toll on the hospital staffs as many of them were anxious and scared.At the same time, Dengue and Scrub Typhus cases also emerged in the district, adding to the health woes. However, the hospital staffs and the local bodies are stepping up to the challenge and are toiling hard to plan and execute for the containment of the disease in the district.